2015
DOI: 10.1002/jcb.25306
|View full text |Cite
|
Sign up to set email alerts
|

FOXD3 Promotes PAX3 Expression in Melanoma Cells

Abstract: Several key transcription factors regulate cell growth, survival, and differentiation during neural crest and melanoblast development in the embryo, and these same pathways may be reactivated in tumors arising from the progenitors of these cells. The transcription factors PAX3 and FOXD3 have essential roles in melanoblasts and melanoma. In this study, we define a regulatory pathway where FOXD3 promotes the expression of PAX3. Both factors are expressed in melanoma cells and there is a positive correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…These observations were in accord with previous studies showing that a subset of Pax3 EGFP cells in the forelimb differentiate into vascular epithelial cells 39 . In limb formation, the vascular and nervous systems develop in parallel to the skeletal system 40 , 41 , and the Pax3 lineage is likely to give rise to cells that will populate different systems 42 , 43 .
Figure 3 Myogenic and non-myogenic cells populate the Pax3 EGFP lineage in the forelimb.
…”
Section: Resultsmentioning
confidence: 99%
“…These observations were in accord with previous studies showing that a subset of Pax3 EGFP cells in the forelimb differentiate into vascular epithelial cells 39 . In limb formation, the vascular and nervous systems develop in parallel to the skeletal system 40 , 41 , and the Pax3 lineage is likely to give rise to cells that will populate different systems 42 , 43 .
Figure 3 Myogenic and non-myogenic cells populate the Pax3 EGFP lineage in the forelimb.
…”
Section: Resultsmentioning
confidence: 99%
“…However, based on previous reports, there are some possible mechanisms to consider. First, FOXO1 and PAX3 might bind directly, as Kubic et al showed that overexpression of FOXD3, a member of the FOX protein family, upregulated PAX3 expression in melanoma cells by the direct binding of FOXD3 to PAX3 promoter [45]. Second, there might be other target genes that are activated or repressed by FOXO1 and PAX3.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, FOXD3 can directly upregulate PAX3 by binding to its promoter [124]. FOXD3 is suppressed by BRAF, and it acts as a cell cycle repressor by upregulating p21 Cip1 [125].…”
Section: Targeted Therapymentioning
confidence: 99%